The Pjateckiǐ-Šapiro prime number theorem - Heath-Brown, D (1983)
It is proved that the sequence [nc] contains the expected number of primes whenever 1 < c < 1.1404..., thus improving Kolesnik's range 1 < c < 1.1111.... An identity of Vaughan's type in five variables is needed. © 1983.